Diffusion and Infusion of Information and Communication Technologies in Kenyan Higher Education - Pelser, Theunis G; Macharia, Jimmy K. N. (South African Journal of Higher Education, 2016)
Previous studies have shown that despite the widespread adoption of information and communication technologies (ICT) in higher education institutions (HEIs) since the mid-1990s, this has failed to produce the fundamental changes in learning and teaching that university management expected, and that it is unclear what factors contribute to ICT acceptance by learners. Consequently, the aim of this study was to answer the question as to what environmental, technological, organizational and individual factors are most likely to influence choice behaviour to use ICT in student learning. Path analysis statistical techniques in Structural Equation Modelling (SEM) were used. The findings show that environmental, technological, organizational and individual factors play a significant role in ICT diffusion and infusion. It was further observed that the effects of some factors including availability of ICT, access to ICT, institution’s chief executive officer (CEO) characteristics play a pivotal role in ICT diffusion in a developing country context. This study produced useful insights into the factors that influence technology acceptance decisions by students and provided new ideas in the management of ICT diffusion and infusion.